Navigating Constraints Indonesian Workers’ Experiences under Korea’s EPS: Indonesian Workers’ Experiences under Korea’s EPS - On, Taihyeon; Iskandar, Kurniawaty (WILAYAH: The International Journal of East Asian Studies, 2025)
This paper explores the experiences of Indonesian migrant workers in terms of job mobility and agency within the Employment Permit System in South Korea. The research relies on Strong Structuration Theory to analyze how external constraints—legislative laws and control by employers—interact with internal factors such as economic goals and sociocultural barriers that impact migrant workers’ decision-making. Semi-structured interviews with Indonesian laborers showed the systemic problems due to sectoral inequalities, such as vulnerabilities brought about in the industry of fishing. Evidence shows restricted job mobility policies heightening the employees’ dependence upon the employer, thus limitations to freedom and encouragement towards precarious situations. Employees try to get through such restrictions by strategic choice and through informal networks. Keywords: Employment Permit System, Job mobility, Strong Structuration Theory, Temporary Labor Migration, Indonesian migrant workers